2024
DOI: 10.1093/schizbullopen/sgae006
|View full text |Cite
|
Sign up to set email alerts
|

Network Structure of Childhood Trauma, Bodily Disturbances, and Schizotypy in Schizophrenia and Nonclinical Controls

Lénie J Torregrossa,
Jinyuan Liu,
Kristan Armstrong
et al.

Abstract: Background and Hypothesis Exposure to childhood trauma has been linked to the development of psychosis and bodily-self disturbances, two hallmarks of schizophrenia. Prior work demonstrated that bodily disturbances serve as a bridge between childhood trauma and schizophrenia symptomatology, but the diagnostic specificity of these connections remains unknown. This study uses network analysis to bridge this gap by comparing the interplays between childhood trauma, bodily-self disturbances, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Further, recent research has identified bodily self-disturbances as the shortest paths from childhood trauma to schizotypal experiences in both schizophrenia patients and healthy individuals ( Torregrossa et al, 2024 ), using the network approach to understanding the multifaceted nature of schizotypy and its relationship to schizophrenia ( Fonseca-Pedrero et al, 2021 ). Future research investigating the applications of MBI for reducing risk factors for conversion to psychosis and schizophrenia in the individuals with high positive schizotypy should include bodily self-disturbances related to childhood trauma as one of the outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent research has identified bodily self-disturbances as the shortest paths from childhood trauma to schizotypal experiences in both schizophrenia patients and healthy individuals ( Torregrossa et al, 2024 ), using the network approach to understanding the multifaceted nature of schizotypy and its relationship to schizophrenia ( Fonseca-Pedrero et al, 2021 ). Future research investigating the applications of MBI for reducing risk factors for conversion to psychosis and schizophrenia in the individuals with high positive schizotypy should include bodily self-disturbances related to childhood trauma as one of the outcome measures.…”
Section: Discussionmentioning
confidence: 99%